Effects of in vitro atmospheric ammonia exposure on recovery rate and luminol-dependent chemiluminescence of bovine neutrophils and bronchoalveolar macrophages - Murata, H. (National Inst. of Animal Health, Shichinohe, Aomori (Japan). Tohoku Branch); Horino, R (Journal of Veterinary Medical Science, 1999)
The effects of atmospheric ammonia, a major pollutant in animal confinement facilities, on bovine neutrophils and bronchoalveolar macrophages were evaluated in vitro. Ammonia exposure at concentrations 50, 100 and 200 ppm for one hour impaired recovery rates of neutrophils dose-dependently but enhanced their chemiluminescence activity per cell at lower concentrations (50 and 100 ppm). Macrophages were resistant to the exposure. Their recovery rates and chemiluminescence remained unaffected even at 200 ppm exposure. The present results suggest that ammonia exposure is unfavorable for bovine neutrophils in vitro, and probably in vivo also, in light of causing cell damage and triggering wider inflammatory responses